Albumin-fused thioredoxin ameliorates high-fat diet-induced non-alcoholic steatohepatitis - Ryota Murata; Hiroshi Watanabe; Ryotaro Iwakiri; Mayuko Chikamatsu; Takao Satoh; Isamu Noguchi; Kengo Yasuda; Ayano Nishinoiri; Takuma Yoshitake; Hiroto Nosaki; Hitoshi Maeda; Toru Maruyama (Heliyon, 2024)
The pathogenesis of non-alcoholic steatohepatitis (NASH) involves the simultaneous interaction of multiple factors such as lipid accumulation, oxidative stress, and inflammatory response. Here, the effect of human serum albumin (HSA) fused to thioredoxin (Trx) on NASH was investigated. Trx is known to have anti-oxidative, anti-inflammatory, and anti-apoptotic effects. However, Trx is a low molecular weight protein and is rapidly eliminated from the blood. To overcome the low availability of Trx, HSA-Trx fusion protein was produced and evaluated the therapeutic effect on high-fat diet (HFD)-induced NASH model mice. HSA-Trx administered before the formation of NASH pathology showed it to have a preventive effect. Specifically, HSA-Trx was found to prevent the pathological progression to NASH by suppressing lipid accumulation, liver injury markers, and liver fibrosis. When HSA-Trx was administered during the early stage of NASH there was a marked reduction in lipid accumulation, inflammation, and fibrosis in the liver, indicating that HSA-Trx ameliorates NASH pathology. The findings indicate that HSA-Trx influences multiple pathological factors, such as oxidative stress, inflammation, and apoptosis, to elicit a therapeutic benefit. HSA-Trx also inhibited palmitic acid-induced lipotoxicity in HepG2 cells. Taken together, these results indicate that HSA-Trx has potential as a therapeutic agent for NASH pathology.